Serum and mucosal antibody-mediated protection and identification of asymptomatic respiratory syncytial virus infection in community-dwelling older adults in Europe - Öner, Deniz; Vernhes, Charlotte; Balla-Jhagjhoorsingh, Sunita; Moureau, Annick; Crabbe, Marjolein; Salaun, Bruno; Bastian, Arangassery Rosemary; Thys, Kim; De Smedt, Jonathan; Ooft, Salo N.; Korsten, Koos; Adriaenssens, Niels; et al. (Frontiers in Immunology, 2024)
Respiratory syncytial virus (RSV) causes acute respiratory tract infection (ARTI) and reinfects adults throughout life, posing a risk for hospitalization in older adults (> 60 years) with frailty and comorbidities. To investigate serum and mucosal antibodies for protection against RSV infections, baseline serum samples were compared for RSV-pre-and post-fusion (F) binding, and RSV-A2 neutralizing IgG antibodies between symptomatic RSV-ARTI (N=30), non-RSV (RSV negative) ARTI (N=386), and no ARTI (N=338). Mucosal RSV-pre-F IgA and IgG levels, as well as serum RSV-G IgG antibodies, were analyzed to determine their association with protection from symptomatic RSV-ARTI in a subset study. Using a receiver operating characteristic (ROC) analysis, we established thresholds of 1.4-to-1.6-fold change (FC) for RSV-pre-and post-F, and RSV-A2 neutralizing IgG antibodies, respectively, enabling the identification of asymptomatic RSV cases with high sensitivity and specificity (> 80% and >90%, respectively). As a result, serum RSV-pre-F, RSV-G IgG, and mucosal pre-F binding IgA antibodies showed correlations with protection against symptomatic RSV infection. RSV-pre-F IgG antibodies were correlated with protection from RSV infections irrespective of the symptoms. This study provides insights into antibody-mediated protection for symptomatic RSV infection in a community-dwelling older-adult population and establishes a threshold to identify asymptomatic RSV infection using a data-driven approach.